An Effort to Improve 4C Students Skills Through STEAM Learning Workshop for Junior High School Teachers in Karanganyar - Budi Usodo; Farida Nurhasanah; Henny Ekana Chrisnawati; Sutopo Sutopo; Yemi Kuswardi (Universitas Sebelas Maret, 2024)
The application of physical distancing during the pandemic has prompted the government to require schools to implement distance learning. One of the learning approaches that can be applied to carry out school activities today is STEAM learning. For this reason, this service activity aims to train junior high school mathematics teachers in Karanganyar district to be able to design study plans, learning media and assessment instruments. Based on this goal, the community service team carried out a workshop activity at Junior High School 1 Kerjo Karanganyar and POKJA II Karanganyar consisting of 25 teachers. There were two resource persons who assisted in the implementation of the workshop about material on the concept and implementation approach and designing a board game for learning. To find out the understanding of the teachers before and after the training, a questionnaire was used. The results of the questionnaire were analyzed using qualitative method. From community service activities, the following results were obtained, the teachers had (1) understood the concept and implementation of STEAM learning; (2) able to develop learning tools in the form of lesson plans, learning media and assessment instruments; (3) implementing limited STEAM learning